Seeing Red: Inside the Science and Politics of the IUCN Red List - Lisa M Campbell (Conservation & Society, 2012)
The Red List of Threatened Species™ (hereafter Red List) is the International Union for the Conservation of Nature′s most recognisable product. The Red List categorises the conservation status of species on a global scale using ′the most objective, scientifically-based information′. Completing Red List assessments is the job of the Species Survival Commission (SSC), and assessments are most often conducted by species specialist groups within the SSC. In the SSC′s Marine Turtle Specialist Group (MTSG), assessments have been contested. Debate is often couched in scientific terms, focused on data availability and the relevance of Red List criteria for marine turtles. However, given the potential conservation impacts of such listings, much more is at stake. In this paper, I analyse an exchange among MTSG members that resulted when the draft Red List assessment for the hawksbill sea turtle was circulated to the group in June 2007. The suggested listing of hawksbill turtles as ′critically endangered′ sparked an email exchange that highlighted not only the scientific, but also the political, economic, and value-based dimensions of the debate. I draw on ideas of co-production and boundary work to analyse both the debate and the MTSG′s response to an associated crisis of legitimacy, and to provide insights into the science-policy interface in conservation.